2021
DOI: 10.1029/2021wr029662
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Particle Image Velocimetry Reveals Pulsing of Incoming Flow at a Stream Confluence

Abstract: Despite widespread recognition that confluences are characterized by complex hydrodynamic conditions, few studies have mapped in detail spatial patterns of flow at confluences and variation in these patterns over time. Recent developments in large‐scale particle image velocimetry (LSPIV) have created novel opportunities to explore the spatial and temporal dynamics of flow patterns at confluences. This study uses LSPIV to map two‐dimensional flow structure at the water surface at a confluence and to examine var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
(155 reference statements)
2
11
0
Order By: Relevance
“…While vertically orientated KH instabilities can be directly observed as swirls of debris or turbidity gradients on a confluence's surface (Biron et al., 2019; De Serres et al., 1999; Duguay et al., 2022; Lewis & Rhoads, 2015), helical cells are apparent only on cross‐sections of the mean flow measured using acoustic velocimetry (Rhoads & Johnson, 2018; Rhoads & Sukhodolov, 2001; Riley et al., 2015; Yuan et al., 2021). Recently, episodic pulses in the confluence's mixing interface have been identified with large‐scale particle image velocimetry (LSPIV) (Sabrina et al., 2021), a discovery highlighting the advantage of spatially resolved instantaneous measurement techniques. Though the causal mechanism of the pulses is not fully understood, they are likely due to unsteadiness in the water‐surface pressure‐gradient field as the flows compete for space within the confluence (Sabrina et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While vertically orientated KH instabilities can be directly observed as swirls of debris or turbidity gradients on a confluence's surface (Biron et al., 2019; De Serres et al., 1999; Duguay et al., 2022; Lewis & Rhoads, 2015), helical cells are apparent only on cross‐sections of the mean flow measured using acoustic velocimetry (Rhoads & Johnson, 2018; Rhoads & Sukhodolov, 2001; Riley et al., 2015; Yuan et al., 2021). Recently, episodic pulses in the confluence's mixing interface have been identified with large‐scale particle image velocimetry (LSPIV) (Sabrina et al., 2021), a discovery highlighting the advantage of spatially resolved instantaneous measurement techniques. Though the causal mechanism of the pulses is not fully understood, they are likely due to unsteadiness in the water‐surface pressure‐gradient field as the flows compete for space within the confluence (Sabrina et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, episodic pulses in the confluence's mixing interface have been identified with large‐scale particle image velocimetry (LSPIV) (Sabrina et al., 2021), a discovery highlighting the advantage of spatially resolved instantaneous measurement techniques. Though the causal mechanism of the pulses is not fully understood, they are likely due to unsteadiness in the water‐surface pressure‐gradient field as the flows compete for space within the confluence (Sabrina et al., 2021). Unlike KH instabilities, helical cells and episodic pulses, a fourth form of coherent flow structure—streamwise orientated vortices (SOVs)—have been suggested to exist yet have eluded detection in situ.…”
Section: Introductionmentioning
confidence: 99%
“…
A greater understanding of these structures is therefore of obvious interest. Four structures are often discussed: helical cells (secondary flow at the scale of the tributaries' widths), vertically orientated Kelvin-Helmholtz (KH) vortices (shear-induced instabilities along the mixing interface), episodic pulses (origins still not fully understood, see Sabrina et al (2021)) and streamwise orientated vortices (SOVs). SOVs were first discovered in numerical models as a pair of back-to-back, counter-rotating SOVs flanking each side of the mixing interface (Constantinescu et al, 2011) and their development is generally attributed to the downwelling of superelevated water, in a process strengthened by planform curvature (Sukhodolov & Sukhodolova, 2019).
…”
mentioning
confidence: 99%
“…The stagnant flow phenomenon is common in large river confluence areas, where the flow is gentle and the water quality conditions are stable. Sabrina et al (2021) found a similar large region of flow stagnation at the junction apex by using large-scale particle image velocimetry. The distribution characteristics in the wet and dry periods were similar.…”
Section: Typical Backflow Characteristics Of Confluence (No Spur Dike)mentioning
confidence: 67%
“…Sabrina et al. (2021) found a similar large region of flow stagnation at the junction apex by using large‐scale particle image velocimetry. The distribution characteristics in the wet and dry periods were similar.…”
Section: Resultsmentioning
confidence: 85%